855. Significance of Invasive Infections due to Methicillin Sensitive Staphylococcus aureus in the neonatal population. (31st December 2020) - Riollano, Mariawy; Altman, Deena; kowalsky, shanna; Pan, Stephanie
Abstract: Background: Staphylococcus aureus is a well-known cause of hospital acquired infections. Methicillin resistant staphylococcus aureus (MRSA) colonization is a recognized risk factor for invasive infections. The neonatal population in the intensive care unit (NICU) is particularly vulnerable to these types of infections, resulting in high mortality and morbidity. However, only scant data is available to establish the risk for invasive disease in patients with Methicillin sensitive staphylococcus aureus (MSSA). As a result, surveillance and prevention strategies are only address for MRSA colonization. Here, we describe the clinical characteristics of S. aureus colonized patients identified in late 2018 during transmission events in a single center NICU. As a result of the targeted surveillance investigation for MRSA infection control measures, S. aureus colonization was stratified, and we were able to compare the differences in invasive disease between MRSA and MSSA. Methods: This is a retrospective chart review of the 47 colonized patients identified during October 2018- January 2019 SA transmission events in single center NICU. Risk factors, clinical characteristics, and the hospital course of these cases, including the proportion of invasive illness were reviewed. Results: We found that most clinical characteristic, risk factors, and hospital course were the same between MRSA and MSSA colonized infants (p values > 0.05). Additionally, there was no difference in the proportion of invasive infection between MRSA and MSSA colonized patients (p value > 0.05). The type of invasive infections identified were SSTI, bacteremia, and osteomyelitis. Conclusion: The proportion of invasive infection was the same in MSSA and MRSA colonized patients. This data provides us with supportive material for future recommendations of infection control measures for MSSA colonized patients. Disclosures: All Authors : No reported disclosures